2014
DOI: 10.1007/s12094-014-1185-7
|View full text |Cite
|
Sign up to set email alerts
|

TGF-beta induced RBL2 expression in renal cancer cells by down-regulating miR-93

Abstract: TGF-beta induced RBL2 expression through down-regulating miR-93 in renal cancer cells. The newly identified TGF-beta/miR-93/RBL2 signal pathway reveals a new mechanism of TGF-beta induced growth arrest in renal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…miR-93, a microRNA frequently associated with TGF-β signaling in controlling cell cycle arrest [ 26 ], cell proliferation, and differentiation [ 27 ], was also down-regulated in both Groups A and B. Moreover, we discovered that miR-1224 and miR-125a-3p, which were initially up-regulated in Group A, became down-regulated at day 3 and 5 in Group B post-induced with IGF-1.…”
Section: Discussionmentioning
confidence: 92%
“…miR-93, a microRNA frequently associated with TGF-β signaling in controlling cell cycle arrest [ 26 ], cell proliferation, and differentiation [ 27 ], was also down-regulated in both Groups A and B. Moreover, we discovered that miR-1224 and miR-125a-3p, which were initially up-regulated in Group A, became down-regulated at day 3 and 5 in Group B post-induced with IGF-1.…”
Section: Discussionmentioning
confidence: 92%
“…Shi, et al found that TGF-β induces RBL2 expression and arrests renal cancer cell growth by downregulating miR-93-5p, and indirectly showed that miR-93-5p suppression induces G1 phase arrest. Wulfken, et al demonstrated that miR-93-5p is upregulated in renal cancer patient serum and tissues, but the miR-93-5p function was not well understood [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, miR-93 abolishes tumor-suppressive TGF-β1 effects, providing an explanation for TGF-β1 resistance in RCC. Intriguingly, TGF-β1 reduces miR-93 expression, which leads to increased RBL2 expression, indicating reciprocal feedback regulation in the TGF-β1-RBL2-miR-93 axis [287]. Furthermore, miR-429 disrupts TGF-β-dependent inhibition of E-cadherin expression, suggestive of an attenuation of TGF-β-induced EMT.…”
Section: Renal Cancermentioning
confidence: 97%